THE ANALYSIS OF UNIT SHIFT IN THE RESEARCH OF TRANSLATION WITH COMMENTARY: ENGLISH INTO INDONESIAN - Fika Agistiawaty (Aksara, 2019)
Unit shift is one of a shift that is found in the translation. Unit shift is a translation strategy that changes the unit of the source text, such as a word into a phrase, a phrase into a clause, and a phrase into a word. This article aims to find out the unit shift in the translation of the novel Counting by 7s that is from English into Indonesian. The methods used in this article are introspective and retrospective method. The procedure of the research were reading the novel, translating it, marking the problem found, taking the problem concerning unit shift to be analyzed, and analyzing the chosen data based on Duff’s principles of translation, Chesterman’s unit shift translation strategy, and theories of languages. The results of this research show that the translation strategy of unit shift can be combined with the translation strategy of expansion, compression, cohesion change, and antonymy. Besides, the unit shift analyzed is only from a word to a phrase and vice versa.